2017
DOI: 10.1111/ene.13356
|View full text |Cite
|
Sign up to set email alerts
|

EAN consensus review on prevention, diagnosis and management of tick‐borne encephalitis

Abstract: Tick-borne encephalitis is a viral CNS infection that may result in long-term neurological sequelae. Since its incidence in Europe is increasing due to broadening of endemic areas and prolongation of the tick activity season, the health burden of TBE is enlarging. There is no effective antiviral treatment for TBE, but the disease may be effectively prevented by vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
212
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 238 publications
(468 reference statements)
4
212
0
5
Order By: Relevance
“…Transmitted by infected ticks, this virus may cause severe neurological symptoms in a form of encephalitis or meningoencephalitis, eventually leading to death or serious disabilities. Over ten thousand cases are registered annually despite the availability of vaccines, and small molecule compounds comprise a promising and highly expected treatment option …”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Transmitted by infected ticks, this virus may cause severe neurological symptoms in a form of encephalitis or meningoencephalitis, eventually leading to death or serious disabilities. Over ten thousand cases are registered annually despite the availability of vaccines, and small molecule compounds comprise a promising and highly expected treatment option …”
Section: Introductionsupporting
confidence: 77%
“…Furano[2, 3‐ d ]pyrimidine nucleosides 6 ‐ 9 and their synthetic precursor analogue 10 showed a specific pattern of antiviral activity. These compounds were previously assessed for inhibition of reproduction of HCV and BVDV (RNA viruses, Flaviviridae family) . The only active compound in these assays was 9 , with EC 50 of 1.9 μM against BVDV and moderate HCV inhibition at 100 μM, without inhibition of RNA‐dependent RNA polymerase NS5B and RNA helicase NS3.…”
Section: Resultsmentioning
confidence: 99%
“…None of the patients had been vaccinated against TBE. Disease was diagnosed based on the clinical picture, presence of inflammatory parameters in the CSF (Table ), and specific antibodies in serum and CSF according to the case definition that is: the presence of clinical signs of meningitis, meningoencephalitis or meningoencephalomyelitis, an epidemiological link, CSF pleocytosis (>5 cells/dl), and demonstration of recent TBEV infection by the presence of specific serum IgM and IgG antibodies (Taba et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Vaccination is an effective measure to prevent morbidity and mortality associated with infectious diseases. This is also the case for TBE where no specific therapy is approved and treatment is supportive only [6]. TBE is also endemic in all Austrian federal states and a vigorous vaccination campaign launched in 1981 can be regarded as a continuing success story [7].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study on TBE in Europe (5205 cases) reported that the condition developed in 87 patients (1.7%) despite those individuals receiving at least two primary vaccination courses [9]. The European vaccines are licensed for adults and children >1 years [6]. They require a primary series of three doses.…”
Section: Introductionmentioning
confidence: 99%